A comparative visual study of Interior Design within prison institutions - Hassim, Lamis (The IIE, 2022)
The consideration of ‘wellbeing’ is a luxury, furthermore, the concept of Interior Design is seen to be one with which the wealthy alone, are acquainted. The understanding of elements within design and their potential power to improve the Subjective Wellbeing of those within the space, is a tool which few consider, specifically when conceptualising spaces which we as a society, use to detain. It is not only necessary, but vital that we consider how the spaces we design impact those who are ordered to be contained within them. It is imperative that we consider how they can affect and how they can improve. This study examines the consideration, or lack thereof of Interior Design within prison institutions in order to argue for its’ benefit. Through the utilisation of case studies, specifically comparing two prisons on either end of the spectrum regarding wealth, recidivism rate as well as population, it was possible to obtain common grounds on which to assess and therefore gather results. The paper explores the elements of ‘good’ design and the analysis of these principles within each of the institutions compared. The purpose of the study aims to catalyse innovative thinking when designing spaces which are generally contested, as well as improve the overall standard of design consideration in prison institutions. The key contributions of the report aim to further understand and develop concepts on the topic while providing a tangible point of comparison when putting theory into practice.
Keywords: Subjective Well-Being; Biophilia; Healing Environments; Good design; Designing spaces; The architecture of prisons; Kriminalomsorgen; Colour and light; Colour Psychology